2018
DOI: 10.1158/0008-5472.can-17-4060
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Citron Kinase Inhibits Medulloblastoma Progression by Inducing Apoptosis and Cell Senescence

Abstract: Medulloblastoma is the most common malignant brain tumor in children. Current treatment for medulloblastoma consists of surgery followed by irradiation of the whole neuraxis and high-dose multiagent chemotherapy, a partially effective strategy associated with highly invalidating side effects. Therefore, identification and validation of novel target molecules capable of contrasting medulloblastoma growth without disturbing brain development is needed. Citron kinase protein (CITK), encoded by primary microcephal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 69 publications
(101 reference statements)
3
41
0
Order By: Relevance
“…3 Another study suggested that citron kinase protein might be a potential target for medulloblastoma treatment. 19 Cytokinesis failure can cause polyploidy, which is an irreversible process that prevents cell division and may lead to a reduction in tumor burden. 20 In contrast, polyploidy can lead to chromosomal instability and increase tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another study suggested that citron kinase protein might be a potential target for medulloblastoma treatment. 19 Cytokinesis failure can cause polyploidy, which is an irreversible process that prevents cell division and may lead to a reduction in tumor burden. 20 In contrast, polyploidy can lead to chromosomal instability and increase tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…MCPH4, MCPH7, MCPH8, MCPH10, MCPH13, MCPH17, MCPH19, and MCPH23 are highly expressed in different tumor tissues or cancer cell lines, indicating that some MCPH genes can be considered as oncogenes or potential cancer biomarkers [24][25][26][27][28][29][30][31]. The knockdown or inhibited expression of these genes may be a potential therapeutic method for cancer treatment [31][32][33]. In addition, the overexpression of MCPH2, MCPH5, MCPH7, MCPH14, MCPH20, MCPH21, MCPH23, and MCPH24 is associated with aggressiveness and poor outcome in patients with cancer [28,[34][35][36][37][38][39].…”
Section: Some Mcph Genes Can Be Considered As Potential Cancer Biomarmentioning
confidence: 99%
“…Apoptosis of neuronal progenitors [76,77] Cell cycle and apoptosis (colon cancer, CC) [26] DNA damage, proliferation, cell senescence and apoptosis (medulloblastoma) [33] MCPH18 (WDFY3)…”
Section: Mcph17 (Cit)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CITK loss leads to accumulation of DNA double strand breaks (DSB), strongly activating the P53 signaling pathway in developing central nervous system [16]. We have shown that CITK loss induces apoptosis and cell senescence in SHH MB cells and reduces growth of both xenograft and transgenic MB [31]. Interestingly, these anti-proliferative effects of CITK loss may be engaged through TP53-dependent and TP53-independent mechanisms [16,31].…”
Section: Introductionmentioning
confidence: 99%